A new allele, HLA‐DQB1*04:09. Issue 3 (19th August 2013) - Testi, M.; Troiano, M.; Guagnano, A.; Testa, G.; Andreani, M.
<x xml:space="preserve">Abstract</x> The novel allele HLA‐DQB1*04:09 differs from DQB1*04:02:01 by three nonsynonymous nucleotide substitutions in exon 2.